Rancang Bangun Sistem Pendeteksi Kebakaran Berbasis SMS Gateway Menggunakan Arduino - Andika Sabilana; Muhammad Misdram (Fakultas Teknologi Informasi Universitas Merdeka Pasuruan, 2021)
The circumstances and natural in the Pasuruan Regency area are in the highlands so that they have hilly land surface contours. Several times there were forest fires that could not be controlled due to lack of information. Therefore we need an automated system that can provide information directly through the sms gateway. SMS communication media can provide notifications so that fire information will not come again because it will come to the field. The goal is to use an Arduino that is connected to a sensor as soon as possible and a fire that will send data with an IoT-based 800l SIM and an sms gateway will be able to cause accidents due to fires because fire information can be known quickly on fire notifications.Keywords— Fire, SIM800l, SMS Gateway